UN LIENZO DEL PINTOR RIOJANO DIEGO DE LEYVA EN CASTAGENA, Y SU FUENTE DE INSPIRACIÓN GRABADA - Agüera Ros, José Carlos (Imafronte, 1985)
The rich artistic patrrmony belonging to the Saint hospital of Charity (Santo Hospital de la Caridad, from Cartagena, keeps a picture showrng St. Lawrence's Martyrdom, clearíy signed LEIVA. This surname is identifiable With such of 'Diego de Leyva,. an artist from La Rioja, working at Burgos between 1628 to 1637, and who finished his life as a monk, joined to the Charterhouse of Miraflores. his personality is until today, one of others among the pictoric background of the Spanish 1600th, and needs to be actualized because the few information available about this artist, shows a great sparsity. The picture we are hereby presenting, has been collected from the artistical repertories. as from Ponz, and it is in perfect concordance with the characteristics of his production, which were obtained from the above sources. Accordingly with that information, there is frequent employement of martyrdom arguments, one of which is represented on this picture. But, it also shows the peculiarity of a very well known composition of Tiziano; (whose influence is found after an engraving made by the flemish. Cornelius Cort of two pictures belonging to the great Italian artist. which are kept, one at Venice and the other at El Escorial. This is available to remember the great infuence of the Venetian artist and his creations in Spain. Al1 this, and the estilistic and interpretative considerations about the painter of la Rioja. Leyva, are the real matter of this article.